ANALISIS PENGARUH BUDAYA ORGANISASI, KOMPETENSI DAN KOMITMEN ORGANISASI TERHADAP KERJA PEGAWAI YANG DIMEDIASI OLEH MOTIVASI KERJA (STUDI PERWAKILAN BPKP PROVINSI JAWA TENGAH) - SUBAGIO, UNTUNG; Miyasto, Miyasto; Idris, Idris (JURNAL BISNIS STRATEGI, 2014)
This study is purposed to analyze the performance of employees BPKP Representative of Central Java Province. The study was conducted to examine the influence of organizational culture, competencies and organizational commitment to employee performance that is mediated by the motivation to work. The study was conducted in Central Java BPKP Representatives, with 105 employee respondents. Data was collected using a questionnaire method is to provide a list of questions or questionnaires directly to the respondents. Data analysis techniques in this study using analysis of Structural Equation Modeling (SEM). The results show organizational culture, competence, and organizational commitment has a positive and significant influence on work motivation in improving employee performance. The influence of organizational culture on motivation is a significant and positive; influence of competence on motivation is a significant and positive; influence of organizational commitment on motivation is a significant and positive; influence of organizational culture on employee performance is significant and positive; competence influence on employee performance is significant and positive; influence of organizational commitment on employee performance is significant and positive, and the effect of work motivation on employee performance is significant and positive.Â